A study on newer technique for reconstruction of pre auricular soft tissue defect with temporo-parietal fascia flap (Khabeer’s flap) - Khabeer, Ahmed Abdul; Ivaturi, Phani Bhushan; Jadhav, Y. L. Ravi; Dasoju, Venkatesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: A pre auricular sinus is a congenital abnormality, which occurs due to failure of fusion of primitive tubercles from which pinna develops. Pre auricular sinuses are usually asymptomatic and when symptomatic present usually as discharging sinus, associated with abscess formation anterior to root of helix. Symptomatic pre auricular sinus requires surgical excision to prevent recurrence and reinfection. Treatment of pre auricular sinus by conventional methods usually presents a dead space due to removal of sinus tract. The present study is to overcome this defect by a superficial temporalartery based temporo-parietal fascia flap or Khabeer’s flap. The objective of this study is to describe a novel technique for excision of pre auricular sinus using supra auricular approach and using a temporo-parietal fascia flap for covering the defect created after excision of pre auricular sinus. Methods: A prospective study was carried out in Department of Otorhinolaryngology, Gandhi Medical College/Gandhi Hospital Secunderabad from 2014 to 2017. All the patients admitted with symptomatic pre auricular sinus underwent surgical excision by supra auricular approach and at the end superficial temporal artery based flap was placed to fill the dead space. Results: A total of 20 pre auricular sinuses were operated during the study period. There were no recurrences, no collection of serous fluid and no cosmetic defect post operatively in any of the study subject. Conclusions: The newer approach was found to be safe as it does not confer any complications post operatively and can be used for management of pre auricular sinus.